Timelines of Tension: Trajectories of Protected-Area Creation in the Austrian Alps - Valerie Braun; Gebhard Bendler; Andreas Haller; Kati Heinrich (Revue de Géographie Alpine)
The establishment of protected areas is often preceded by tensions and intense discussions between stakeholders of differing interests. Governmental bodies, environmental conservation groups and local actors, such as farmers or locals involved in tourism, are either in favour of or in opposition to the designation of protected areas in their home regions. Using two protected areas in the Eastern Austrian Alps as cases in point, the present study combines the methods of oral history and archival research to trace these timelines of tension and to identify the actors involved and the issues debated on the way to designation. Our results reveal the complex nature of both cases shaped by a variety of actors from the public, non-profit (or voluntary) and private sectors. After up to 30 years of discussions, both protected areas now seem to be accepted by large parts of the local population and are even well-integrated in the regional agrarian and touristic setting. To shorten these “timelines of tension” in future conservation projects, communication measures and strategies could clearly be improved and past experiences of protected area designations made available to present policy makers of the Alpine region. In this way, new protected areas could be established without undue tensions and pave the way for sustainable development in sensitive environments of the European Alps.